The Enigma of Interspecific Plasmodesmata: Insight From Parasitic Plants - Fischer, Karsten; Lachner, Lena Anna-Maria; Olsen, Stian; Mulisch, Maria; Krause, Kirsten (Frontiers in Plant Science, 2021)
Parasitic plants live in intimate physical connection with other plants serving as their hosts. These host plants provide the inorganic and organic compounds that the parasites need for their propagation. The uptake of the macromolecular compounds happens through symplasmic connections in the form of plasmodesmata. In contrast to regular plasmodesmata, which connect genetically identical cells of an individual plant, the plasmodesmata that connect the cells of host and parasite join separate individuals belonging to different species and are therefore termed “interspecific”. The existence of such interspecific plasmodesmata was deduced either indirectly using molecular approaches or observed directly by ultrastructural analyses. Most of this evidence concerns shoot parasitic Cuscuta species and root parasitic Orobanchaceae, which can both infect a large range of phylogenetically distant hosts. The existence of an interspecific chimeric symplast is both striking and unique and, with exceptions being observed in closely related grafted plants, exist only in these parasitic relationships. Considering the recent technical advances and upcoming tools for analyzing parasitic plants, interspecific plasmodesmata in parasite/host connections are a promising system for studying secondary plasmodesmata. For open questions like how their formation is induced, how their positioning is controlled and if they are initiated by one or both bordering cells simultaneously, the parasite/host interface with two adjacent distinguishable genetic systems provides valuable advantages. We summarize here what is known about interspecific plasmodesmata between parasitic plants and their hosts and discuss the potential of the intriguing parasite/host system for deepening our insight into plasmodesmatal structure, function and development.